Anthropogenic disturbance impact on the stem growth of Prosopis flexuosa DC forests in the Monte desert of Argentina: A dendroecological approach - Piraino, Sergio (2017)
Anthropogenic disturbance acts globally as an ecological process with long-term implication on the ecosystem equilibrium. In the central-western Argentina (Desierto del Monte Central: DMC), the desert Prosopis flexuosa woodlands has been intervened by man with differential incidence, e.g. through logging, fire and grazing. Despite recognizing a history of disturbances in these forests, the local removal of trees and its incidence in the stem growth of the surviving trees is still poorly known. Dendroecological methods were applied to 10 plots distributed along a landform gradient, aiming to analyze how disturbance, together with possible modulation effects of the spatial variability on growth, can influence forest dynamics. Tree removal was an intensive practice during the second half of the 20th century in the DCM, in synchrony with the expansion of wine-growing activity. Our results suggest that removal of P. flexuosa individuals in any considered plot was the main driver of changes in the forest dynamics. This argument is based on the weak climatic incidence in years considered critical with respect to the beginning of abrupt tree-growth releases. This disturbance impact seemed to be landform-dependent, as suggested by the higher relative basal area values at mesic sites in relation to sites linked to drier landforms. The presented findings represent the first attempt in reconstructing the disturbance regime experienced by the DMC P. flexuosa woodlands. Our research contributes to interpret how logging practices coupled with landform-related heterogeneities may influence the forest dynamics at desert environments, providing elements for implementing policies for conservation and management of these natural resources.